A bacteriological study of hospital beds before and after disinfection with phenolic disinfectant - Andrade, Denise de; Angerami, Emília L. S.; Padovani, Carlos Roberto [UNESP] (FapUNIFESP (SciELO), 2000)
In hospitals, one of the ways to control microbial contamination is by disinfecting the furniture used by patients. This study's main objective was to evaluate the microbiological condition of hospital mattresses before and after such disinfection, in order to identify bacteria that are epidemiologically important in nosocomial infection, such as Staphylococcus aureus and Pseudomonas aeruginosa. RODAC plates with two different culture media were used to collect specimens. Patient beds were selected according to previously established criteria, and surface areas on the mattresses were chosen at random. From the total of 1 040 plate cultures from 52 mattresses, positive results were obtained from 500 of them (48.1%), 263 before disinfection and 237 after disinfection. Considering the selectivity of the culture media, the positivity rate was high. There were high prevalences of S. aureus both before and after mattress disinfection. The study results suggest that the usual disinfection procedures, instead of diminishing the number of microbes, merely displace them from one part of the mattress to another, and the number of microorganisms remains the same.
Keywords: disinfectant agent; phenol derivative; bacteriology; bacterium colony; bacterium contamination; controlled study; disinfection; hospital bed; hospital infection; infection prevention; nonhuman; Pseudomonas aeruginosa; Staphylococcus aureus; Bacteria; Bacteriological Techniques; Beds; Brazil; Culture Media; Disinfectants; Disinfection; Phenols